Dehydrogenative Cross-Coupling Reactions of N-Aryl α-Amino Acid Esters with Nitroalkanes for the Synthesis of β-Nitro α-Amino Acid Esters - Zhu, Zhi-Qiang; Xie, Zong-Bo; Le, Zhang-Gao (Synlett, 2017)
A novel copper-catalyzed dehydrogenative cross-coupling reaction of N-aryl α-amino acid esters with nitroalkanes to give β-nitro α-amino acid esters was developed. Various N-aryl α-amino acid esters reacted smoothly with nitroalkanes to give the desired coupling products in moderate to good yields. The method uses a cheap and simple copper salt as a catalyst and molecular oxygen as an environmentally benign oxidant. A possible mechanism for the dehydrogenative cross-coupling reaction is proposed.
Keywords: dehydrogenation; cross-coupling; copper catalysis; amino acid esters; nitroalkanes